Refining latent multi-view graph for relation extraction - Xue, Fuzhao (Nanyang Technological University, 2021)
Relation extraction (RE) is to predict the relation type of two entities that are mentioned in a piece of text, e.g. a sentence or a dialogue. According to various text input formats, Relation extraction can be divided into different categories, such as sentence-level RE, document-level RE and dialogue-level RE. In this thesis, we focus on addressing sentence-level RE and dialogue-level RE with a unified model. For both sentence-level RE and dialogue-level RE, the main challenge arise when the given text is long. It is difficult to identify indicative words for the relation prediction.